2018
DOI: 10.1073/pnas.1713027115
|View full text |Cite
|
Sign up to set email alerts
|

RNA force field with accuracy comparable to state-of-the-art protein force fields

Abstract: SignificanceThe complex and often highly dynamic 3D structures of RNA molecules are central to their diverse cellular functions. Molecular dynamics (MD) simulations have played a major role in characterizing the structure and dynamics of proteins, but the physical models (“force fields”) used for simulating nucleic acids are substantially less accurate overall than those used in protein simulations, creating a major challenge for MD studies of RNA. Here, we report an RNA force field capable of describing the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
372
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(395 citation statements)
references
References 77 publications
18
372
5
Order By: Relevance
“…As part of our study, we tested the recently published ff by D. E. Shaw and co-workers. 60 We applied this ff for folding simulations of RNA TLs with short A-RNA stems as well as for standard simulations of selected RNA motifs. We observed major instabilities caused by this ff version in folded RNAs.…”
Section: Starting Structures and Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our study, we tested the recently published ff by D. E. Shaw and co-workers. 60 We applied this ff for folding simulations of RNA TLs with short A-RNA stems as well as for standard simulations of selected RNA motifs. We observed major instabilities caused by this ff version in folded RNAs.…”
Section: Starting Structures and Simulation Setupmentioning
confidence: 99%
“…4 . Another RNA ff modification (abbreviated as DESRES here) has been published recently, 60 reparametrizing the non-bonded as well as dihedral terms of the AMBER RNA ff and complementing the resulting parametrization with a specific water model. 109 We have tested this ff (see Supporting Information for full details) with the following results.…”
Section: Rest2mentioning
confidence: 99%
“…All these operations have been performed on an 8 CPU (Intel R Xeon R CPU E5-1620 3.50 GHz) Linux workstation. Molecular dynamics (MD) simulations were performed with an ACEMD engine (Harvey et al, 2009) on a GPU cluster composed of 18 NVIDIA drivers whose models go from GTX 980 to Titan V. For all the simulations, the ff14SB force field with χ modification tuned for RNA (χOL3) was adopted to describe ribonucleic acids, while a general Amber force field (GAFF) was adopted to parameterize small organic molecules (Wang et al, 2006;Sprenger et al, 2015;Tan et al, 2018).…”
Section: Software Overviewmentioning
confidence: 99%
“…Although simulation studies of the intact HBV capsid have shown that the inherent flexibility of some virus structures may limit the ability to obtain true atomic (1–2 ˚ A) resolution with cryo-EM [116], advances in image processing are enabling high-resolution asymmetric reconstructions capable of producing m o r e authentic descriptions of encapsidated genome, such as those obtained for the immature HBV particle and bacteriophage MS2 [142, 143]. The availability of more complete structural information, along with improved understanding of genome organization within capsids [144] and integrative modeling approaches [1] that employ increasingly accurate protein and nucleic acid force fields [145, 146], will support new simulation studies of all-atom virions in the near future, particularly for non-enveloped viruses.…”
Section: Toward All-atom Simulations Of Complete Virionsmentioning
confidence: 99%